Wake up to the gender gap in academic anesthesiology and address the pipeline. Issue 1 (2nd January 2023) - Marroquin, Bridget M.
Abstract: Diversity, equity, and inclusion are important values in health care and academic medicine. Although women have comprised nearly 50% of all US medical school graduates since the early 2000s, gender disparities continue in many specialties and persist in medical education leadership. For women in anesthesiology, gender inequities exist along the academic pipeline, with greater disparity in the higher ranks of academia and leadership. Successful endeavors to improve gender equity in the specialty include increasing awareness, engaging in faculty development, and encouraging transparent promotions processes. The strides will be short and change will be slow unless we shift focus to when the gender imbalance begins—at the transition from undergraduate medical education to graduate medical education. Currently women comprise 37% of academic anesthesiology faculty; however, the current resident pool is only 33% women. If recruitment of a gender-equitable workforce at the undergraduate-to-graduate medical education transition is not a priority, the downstream measures will have minimal impact toward gender equity in academic anesthesiology.